Konseling Sebaya Sebagai Wasilah Hisbah Dalam Mengatasi Pelanggaran Mahasiswi di Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah Sukabumi - Hidayat, Tatang; Naeli Sa’adah; Istianah (Fakultas Dakwah Intitut Agama Islam Riyadlotul Mujahidin Ngabar (IAIRM) Ponorogo, 2024)
In this day and age, evil occurs in every crevice of human life. It has become a custom and is considered normal. Responding to this problem, it is necessary to have an amar ma'ruf nahi mungkar or commonly referred to as hisbah/ihtisab. Where hisbah/ihtisab requires an appropriate wasilah in order to achieve optimal results. The purpose of this study is to analyze peer counseling as a wasilah hisbah in overcoming female students' violations at STIBA Ar Raayah. The type of approach taken in this research is a descriptive qualitative approach with data processing from literature review sources and interviews. Data analysis is done by means of interactive analysis. The result of this study is that peer counseling is a suitable means in the context of optimizing hisbah. Peer counseling can be grouped into two forms, namely through group counseling and night reflection.